Life cycle cost - Abdul Rashid, Khairuddin; Ayob, Mohd Fairullazi (2016)
LCC has been mandated by the Malaysia Government as a tactical tool in assessing alternatives being considered in the line of the Government objectives, to advise and facilitate the Government in planning and managing the newer approaches and techniques of project delivery system, i.e. Public Private Partnership (PPP), Value Management (VM), Facilities Management (FM), sustainable building, the Industrialised Building Systems (IBS) and the Red Book procurement system of the Government-Linked Companies (GLCs). The Government and clients, including estimators, and researchers have seen the important use of LCC analysis to facilitate them in making better investment decisions to attain the most optimum total ownership cost of an asset.